Trick or Treat: Does a Microfinance Loan Induce or Reduce the Chances of Spousal Violence against Women? Answers from India - Sinha, Debashree (Journal of interpersonal violence, 2022)
It is a common belief that microfinance plays a dual role of poverty alleviation and socioeconomic upliftment of its women participants. However, there are enough researches that negates the positive impact of microfinance loans on spousal violence. Recognized as one of the most predominant social evils, violence against women is not only a violation of their human rights but also an act of exploitation and denial of freedom. In the present study, we have tried to investigate if microfinance loan takers experience more spousal violence as compared to their counterparts by analyzing the National Family Health Survey IV, 2015?16. Our results indicate that 40.8% of women microfinance participants experience spousal violence. Additionally, the likelihood of microfinance participants to experience spousal violence is much higher than the non-microfinance participants (odds ratio = 1.35, p value = .000). Microfinance programs are designed to increase the individual agencies of women participants, which, in turn, reduce the chances of them becoming victims of spousal violence. However, if the credit program participation induces the woman to be a victim of spousal violence together with becoming financially autonomous, then such hidden costs need to be taken into account while evaluating the effectiveness of the gendered policy design.